Wayang Kulit Lakon Sang Tetuka sebagai Alat Kontrol Sosial di Kalangan Generasi Muda - Paramesti, Niki Nugrah; Sulanjari, Bambang (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2026)
Wayang kulit is an Indonesian cultural heritage that plays a strategic role as a medium for value education and social control within society. This study aims to analyze the wayang kulit play Sang Tetuka as an instrument of social control among the younger generation using Travis Hirschi’s social control theory. The research employs a descriptive qualitative approach, with data collected through performance observation, analysis of play transcripts, and documentation. The data were analyzed using content analysis techniques to identify moral values and mechanisms of social control embedded in the play. The findings indicate that Sang Tetuka contains mechanisms of social control reflected in Hirschi’s four elements of social bonds: attachment (emotional ties of the characters to family values), commitment (commitment to norms of justice), involvement (engagement in responsible actions), and belief (belief in a moral value system). The play conveys messages of social control regarding arrogant behavior among the younger generation, the importance of impartial justice, and the consequences of deviant actions. The wayang kulit performance of this play is proven to be effective as an informal social control medium that can shape the moral awareness of the younger generation through rich and meaningful symbolic narratives.